DESCRIPTIONS AND DIFFERENCES IN STUDENT PERCEPTIONS OF THE PHYSICS-MATHEMATICAL ELECTRONIC MODULE - Putri Ayu Rivani; Astalini Astalini; Darmaji Darmaji (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2023)
This research was conducted with the aim of being able to describe students' perceptions of the mathematics physics electronics module and to know the differences in students' perceptions between Regular A and B classes in the mathematics physics electronics module. This research was conducted using a mix method approach. The total sample is 60 students from two classes. The significant difference between the two classes and the correlation results show that the perception of regular classes A and B has a relationship so that this will affect the usefulness of the physics-mathematical e-module later. And currently students are feeling confused in understanding mathematics physics lessons. Students need teaching materials that are very interesting and of course easy to understand starting from the language, explanations and material. Because the better the positive perception that students give, the students feel that they really need an electronic module to be used in the mathematics physics learning.